2021
DOI: 10.1111/hel.12862
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to international guidelines for the management ofHelicobacter pyloriinfection among gastroenterologists and gastroenterology fellows in Italy: A Survey of the Italian Federation of Digestive Diseases ‐ FISMAD

Abstract: Background Information on the management of Helicobacter (H.) pylori infection by gastroenterologists and gastroenterology fellows are scarce. We aimed to assess practice of gastroenterologists and gastroenterology fellows and their adherence to guidelines for diagnosis and treatment of H. pylori infection in Italy. Materials and Methods All gastroenterologists and gastroenterology fellows attending the National Congress of Digestive Diseases ‐ FISMAD were invited to fill‐in an on‐line questionnaire. The quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(153 reference statements)
0
0
0
Order By: Relevance
“…However, these are challenging topics of interest that require further research in Jordan. A comparable study conducted in Italy found that Italian gastroenterologists adhere to international guidelines for the management of H. pylori infection [ 33 ]. The current study demonstrated unsatisfactory results regarding attitudes and practices among the Jordanian population, which is inconsistent with other studies done in the UAE and China [ 16 , 24 ], highlighting the pervasiveness of this global problem and the need to address it.…”
Section: Discussionmentioning
confidence: 99%
“…However, these are challenging topics of interest that require further research in Jordan. A comparable study conducted in Italy found that Italian gastroenterologists adhere to international guidelines for the management of H. pylori infection [ 33 ]. The current study demonstrated unsatisfactory results regarding attitudes and practices among the Jordanian population, which is inconsistent with other studies done in the UAE and China [ 16 , 24 ], highlighting the pervasiveness of this global problem and the need to address it.…”
Section: Discussionmentioning
confidence: 99%